2022
DOI: 10.3390/brainsci12091154
|View full text |Cite
|
Sign up to set email alerts
|

The Interrelation between Interleukin-2 and Schizophrenia

Abstract: Interleukin-2 (IL-2) is a growth factor that regulates T-cell autocrine secretion and has long been considered to be closely related to immune response. With the advance in neuroinflammation theory and immunology research on schizophrenia, it is interesting and meaningful to discuss the possible role of IL-2 in schizophrenia. Here, we reviewed a series of studies published from the 1990s and found that IL-2 was closely associated with schizophrenia. For example, IL-2 is responsible for mediating toxic reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…The change of IL-2 levels in patients with schizophrenia was found to be an increase in patients with schizophrenia in some research [ 46 ], while others found a decrease [ 63 , 64 ]. During the acute period IL-2 changes significantly, while it tends to stabilize in patients in a stable stage [ 65 ]. IL-2 is a cytokine necessary for the survival and proliferation of regulatory T cells expressing Foxp3+.…”
Section: Discussionmentioning
confidence: 99%
“…The change of IL-2 levels in patients with schizophrenia was found to be an increase in patients with schizophrenia in some research [ 46 ], while others found a decrease [ 63 , 64 ]. During the acute period IL-2 changes significantly, while it tends to stabilize in patients in a stable stage [ 65 ]. IL-2 is a cytokine necessary for the survival and proliferation of regulatory T cells expressing Foxp3+.…”
Section: Discussionmentioning
confidence: 99%
“…We also found an increase in serum IL-2 concentration in schizophrenia (Figure 1B). It is known that IL-2 may play a role in the pathogenesis of schizophrenia in the context of the T-reg hypothesis [43]. However, studies of the concentration of IL-2 in the blood of patients show conflicting results [43].…”
Section: Group Differences In Biomarker Levelsmentioning
confidence: 99%
“…In schizophrenia, impaired Treg cells cause astroglial overactivation and microglial pruning. In the development of Treg cells, interleukin (IL)‐2 is crucial 12 …”
Section: Schizophreniamentioning
confidence: 99%